The Role of Financial Technology in Transforming Business Models in the Banking Sector - Sifera Patricia Maithy; Evinalia Yeba; Pratiwi Hamzah; Dhina Sri Widyaningsih (Journal of Economic Education and Entrepreneurship Studies, 2025)
This research aims to explore the role of Financial Technology (FinTech) in changing business models in the banking sector, particularly at Bank Kalimantan Tengah. FinTech, as part of the digital financial industry revolution, offers a range of innovative services capable of improving operational efficiency and financial inclusion. This research uses a qualitative approach with a case study method that includes in-depth interviews, field observations, and analysis of related documents. The results show that the implementation of FinTech has successfully reduced operational costs by up to 15%, accelerated transaction processes, and provided more practical services for customers. However, significant challenges have also emerged, mainly related to uneven digital infrastructure, low digital literacy, and customer data security that still needs to be improved. The research also found that great opportunities exist through the application of FinTech, such as expanding market share, increasing financial inclusion in remote areas, and developing innovative financial service products. Future FinTech development strategies include improving digital infrastructure, strengthening information security systems, and intensive training for human resources. Strategic collaboration with non-bank FinTech companies is recommended to accelerate technological innovation and digital banking services. Thus, Central Kalimantan Bank is expected to be able to face the challenges of competition in the digital era while contributing to local and national economic growth.